2009
DOI: 10.1111/j.1439-037x.2008.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arbuscular Mycorrhizae in the Alleviation of Ionic, Osmotic and Oxidative Stresses Induced by Salinity in Cajanus cajan (L.) Millsp. (pigeonpea)

Abstract: Salinity stress causes ion toxicity and osmotic imbalances, leading to oxidative stress in plants. Arbuscular mycorrhizae (AM) are considered bio‐ameliorators of saline soils and could develop salinity tolerance in crop plants. Pigeonpea exhibits strong mycorrhizal development and has a high mycorrhizal dependency. The role of AM in enhancing salt tolerance of pigeonpea in terms of shoot and root dry weights, phosphorus and nitrogen contents, K+ : Na+, Ca2+ : Na+ ratios, lipid peroxidation, compatible solutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(58 citation statements)
references
References 76 publications
12
46
0
Order By: Relevance
“…Sodium ion has antagonistic relationship with several other ions like potassium. In present study higher concentration of sodium and lowered concentrations of other ions like potassium, phosphorus, magnesium under salt stress is in concurrence with the findings of Hashem et al, (2015) for tomato and Garg and Manchanda (2009) for Cajanus cajan. AMF not only reduced the deleterious effect of excess sodium by reducing its uptake but also caused a significant increase in uptake of other important mineral elements like potassium, phosphorous, calcium and magnesium.…”
Section: Membrane Stability Index and Malonaldehyde (Mda)supporting
confidence: 93%
“…Sodium ion has antagonistic relationship with several other ions like potassium. In present study higher concentration of sodium and lowered concentrations of other ions like potassium, phosphorus, magnesium under salt stress is in concurrence with the findings of Hashem et al, (2015) for tomato and Garg and Manchanda (2009) for Cajanus cajan. AMF not only reduced the deleterious effect of excess sodium by reducing its uptake but also caused a significant increase in uptake of other important mineral elements like potassium, phosphorous, calcium and magnesium.…”
Section: Membrane Stability Index and Malonaldehyde (Mda)supporting
confidence: 93%
“…The findings of the present study have shown that plants with PGPR association have lower electrolytic concentrations than control plants under salinity and drought stress. This indicates a lower permeability of the plasma membrane mainly attributed to the integrity and stability of cellular tissues by the PGPR interactions compared with non-PGPR interactions (Garg & Manchanda 2009).…”
Section: Discussionmentioning
confidence: 92%
“…Environmental stresses can establish higher electrolytes discharge (like K ions) through displacement of membrane-associated Ca from plasma lemma. Resultantly, membrane permeability is damaged and aggregate higher efflux of electrolytes inside plant cell/tissues (Garg & Manchanda 2009). The findings of the present study have shown that plants with PGPR association have lower electrolytic concentrations than control plants under salinity and drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of lipid peroxidation and maintenance of membrane integrity has been considered as one of the key processes in salinity tolerance (Garg and Manchanda 2009). The measurement of electrolyte leakage from plant tissues is a classical method to estimate membrane integrity in response to environmental stresses, senescence, fruit ripening, etc.…”
Section: Discussionmentioning
confidence: 99%